Barium titanate-based high-entropy dielectric ceramic as well as preparation method and application thereof

By optimizing the chemical composition and process flow of barium titanate-based high-entropy dielectric ceramics, ceramics with low dielectric loss and excellent dielectric properties were prepared, which solved the problem of large dielectric loss of existing materials and achieved wide temperatures High efficiency energy storage and stable dielectric performance within range.

CN119409501APending Publication Date: 2025-02-11XIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411576710.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing barium titanate-based multilayer dielectric materials have large dielectric losses, which seriously limits their commercial applications.

Method used

The chemical composition formula of barium titanate-based high-entropy dielectric ceramic is (Ba0.8Bi0.2)(Ti0.58Zr0.14Sc0.18Mg0.04Nb0.05Ta0.01)O3-xSr0.7M´0.2TiO3, by optimizing x The numerical value and element incorporation content of the product are prepared by combining pretreatment, post-treatment and high-temperature solid-phase sintering processes.

Benefits of technology

Within a wide temperature range of -50℃ to 300℃, the dielectric loss of barium titanate-based high-entropy dielectric ceramics is always ≤0.02, with good temperature stability, high energy storage efficiency and good dielectric properties, which solves the problem of current There is a problem of large dielectric loss of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409501A_ABST
    Figure CN119409501A_ABST
Patent Text Reader

Abstract

The invention discloses barium titanate-based high-entropy dielectric ceramic as well as a preparation method and application thereof, and belongs to the technical field of dielectric energy storage ceramic materials. According to the barium titanate-based high-entropy dielectric ceramic disclosed by the invention, element volatilization in the sintering process is compensated by optimizing the numerical value of x, and meanwhile, the doping content of the elements is regulated and controlled, so that the barium titanate-based high-entropy dielectric ceramic is favorable for simultaneously obtaining excellent energy storage performance and dielectric property, and has excellent dielectric property; the barium titanate-based high-entropy dielectric ceramic is favorable for obtaining ceramics with lower loss and smaller dielectric fluctuation, has good temperature stability, low remanent polarization, large effective energy storage density and excellent dielectric properties, and solves the technical problem of large dielectric loss of the existing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dielectric energy storage ceramic materials, and specifically relates to a barium titanate-based high-entropy dielectric ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, capacitors have been widely used in the field of industrial production. Ceramic capacitors have the characteristics of high operating temperature, good moisture resistance, large specific capacity and low dielectric loss (in the case of ceramics with low dielectric constant), and their capacitance-temperature coefficient can be selected in a wide range. At present, commercial ceramic capacitors with high dielectric constant are BaTiO 3 base ceramic capacitors. However, BaTiO 3 It is widely used in current capacitors, but its dielectric constant has large fluctuations and high losses, and its low Curie temperature limits its application at high temperatures. High entropy has four major effects, namely, the high entropy effect in thermodynamics, the lattice distortion effect in crystallography, the hysteresis diffusion effect in kinetics, and the cocktail effect in performance, which are very helpful in adjusting the local structure and macroscopic performance of the material. In order to enhance the energy storage properties of dielectric materials, various strategies have been proposed in the prior art, such as chemical doping, domain engineering, microstructure engineering, etc. to improve the dielectric constant and breakdown electric field (E b ). Inspired by high entropy alloys, people gradually introduced multi-principal high entropy strategies into the design of ceramic materials, hoping to obtain ceramic materials with better dielectric energy storage performance. Therefore, how to adjust the structure through high entropy strategies to improve its energy storage performance and dielectric properties is a very promising development direction.

[0003] The Chinese patent application with publication number CN 118063207 A discloses a high energy storage density barium titanate-based multilayer dielectric material. 3 The high entropy design of the BaTiO-based dielectric ceramic components can improve its breakdown field strength. However, the barium titanate-based multilayer dielectric material still has the problem of large dielectric loss, which seriously limits its further commercial application. Therefore, the end-member regulation and high entropy strategy are used to synergistically regulate BaTiO 3 The dielectric loss and dielectric constant of ceramic-based capacitors have great commercial value. Summary of the invention

[0004] The purpose of the present invention is to provide a barium titanate-based high-entropy dielectric ceramic and a preparation method and application thereof, so as to solve the technical problem of large dielectric loss of existing materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a barium titanate-based high entropy dielectric ceramic, wherein the chemical composition general formula of the barium titanate-based high entropy dielectric ceramic is (Ba0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 - x Sr 0.7 M´ 0.2 TiO 3 ; in, x =0~0.12; M´ is a trivalent element, and the trivalent element is Bi 3+ ,La 3+ and Sm 3+ Any of .

[0006] The present invention also discloses a method for preparing the above-mentioned barium titanate-based high-entropy dielectric ceramic, comprising the following steps: According to the stoichiometric ratio of the chemical composition formula of barium titanate-based high entropy dielectric ceramics, weigh the raw material Ba 2 CO 3 、Bi 2 O 3 ,La 2 O 3 、 2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O 3 、MgO、Sm 2 O 3 and TiO 2 ; Pre-treating the weighed raw materials to obtain a ceramic powder precursor; After post-processing the ceramic powder precursor, a flaky ceramic is obtained; The flaky ceramics are sintered to obtain barium titanate-based high-entropy dielectric ceramics.

[0007] Furthermore, the pretreatment includes a ball milling treatment, a grinding and drying treatment with anhydrous ethanol medium, and a pre-calcination treatment performed in sequence.

[0008] Furthermore, the grinding and drying process takes 8-24 hours; The pre-sintering treatment is sintering at 800-850° C. for 1-3 hours.

[0009] Furthermore, the post-processing includes ball milling, tableting and cold isostatic pressing performed in sequence.

[0010] Furthermore, the tableting pressure is 1-5 Pa, and the holding time is 1-3 min; The pressure during the cold isostatic pressing process is 100-300 MPa, and the pressure holding time is 1-5 min.

[0011] Furthermore, the ball milling treatment is carried out at a rotation speed of 100-500 r / min and for a time of 10-24 h.

[0012] Furthermore, the sintering process is performed at 1100-1200° C. for 1-4 hours.

[0013] Furthermore, the raw material Ba 2 CO 3 、Bi 2 O 3 ,La 2 O 3 、 2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O 3 、MgO、Sm 2 O 3 and TiO 2 The purity is not less than 99%.

[0014] The present invention also discloses the application of the above-mentioned barium titanate-based high entropy dielectric ceramic in a dielectric energy storage capacitor, characterized in that when the application temperature is within a range of -50°C to 300°C, the dielectric loss of the barium titanate-based high entropy dielectric ceramic in the dielectric energy storage capacitor is always ≤0.02.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a barium titanate-based high entropy dielectric ceramic, which is optimized x The value compensates for the volatilization of elements during the sintering process and at the same time regulates the doping content of the elements, which is beneficial to simultaneously obtain excellent energy storage performance and dielectric properties. The barium titanate-based high-entropy dielectric ceramics have excellent dielectric properties, which is beneficial to obtain ceramics with lower losses and smaller dielectric fluctuations. The barium titanate-based high-entropy dielectric ceramics have good temperature stability, low residual polarization, high effective energy storage density and excellent dielectric properties, which solves the technical problem of large dielectric loss of existing materials.

[0016] The present invention also discloses a method for preparing the above-mentioned barium titanate-based high-entropy dielectric ceramic. Since pretreatment, post-treatment and high-temperature solid-phase sintering (sintering treatment) and other processes are adopted in the preparation process, compared with traditional preparation processes such as solid-phase reaction method and sol-gel method, the sample prepared by this preparation method is denser and has the characteristics of fewer holes, small grains, low loss, high breakdown electric field resistance and good mechanical properties.

[0017] Furthermore, the preparation method disclosed in the present application adopts processes such as high-speed ball milling with a planetary ball mill, cold isostatic pressing and densification, and high-temperature solid-phase sintering (sintering treatment). Compared with traditional preparation processes such as solid-phase reaction method and sol-gel method, the sample prepared by this preparation method is more dense, with fewer holes, small grains, low loss, high breakdown electric field resistance, and good mechanical properties; wherein, the use of a planetary ball mill for high-speed ball milling for more than 12 hours can make the raw material particles more fine and uniform, which is conducive to the synthesis of a uniform pure phase precursor. Cold isostatic pressing treatment at 100-300 MPa can make the ceramic powders more closely bonded, eliminate more pores, and facilitate the densification of the subsequent sintering process. The high-temperature solid-phase sintering in the final stage is conducive to the ceramic formation, and a dielectric ceramic sheet with small grain size, few holes, clear grain boundaries, and high resistance is obtained; the energy storage performance and dielectric properties of dielectric ceramics are simultaneously improved through formulation and process optimization.

[0018] Furthermore, anhydrous ethanol was used as the medium and the raw materials were ground by a planetary ball mill and then subjected to secondary ball milling, the purpose of which was to make the raw materials uniformly mixed, and the raw material particle size was further reduced by high-speed ball milling, which was beneficial to the subsequent sintering reaction. The sample was treated by pre-sintering and secondary sintering, the principle of which was to use high temperature to increase the driving force to make the chemical elements diffuse and react with each other, so that the ceramics formed phases and porcelain, and finally prepared the target component ceramics.

[0019] The present invention also discloses the application of the above-mentioned barium titanate-based high-entropy dielectric ceramic in dielectric energy storage capacitors. According to relevant experimental results, the barium titanate-based high-entropy dielectric ceramic of the present invention has the outstanding characteristics of ultra-low dielectric loss (dielectric loss is always ≤0.02) in a wide temperature range of -50°C to 300°C, stable dielectric constant, breakdown resistance, and high energy storage efficiency, and can be widely used in the field of dielectric energy storage capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an X-ray diffraction spectrum of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 of the present invention; Wherein: a-XRD spectrum of ceramic component in the range of 10-80°; b-XRD (111) peak magnification of ceramic component in the range of 38-39°; Figure 2This is a scanning electron microscope image of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 of the present invention; Among them: a-cross-sectional scanning diagram of BTH component ceramics; b-cross-sectional scanning diagram of BTH-0.04SLT component ceramics; c-cross-sectional scanning diagram of BTH-0.08SLT component ceramics; d-cross-sectional scanning diagram of BTH-0.12SLT component ceramics; Figure 3 This is the temperature-dependent Raman spectrum of the barium titanate-based high-entropy dielectric ceramic prepared in Example 2 of the present invention; Wherein: a-Raman spectrum of BTH-0.08SLT component ceramics from -60℃ to 240℃; b-Raman spectrum peak position of BTH-0.08SLT component ceramics changing with temperature; Figure 4 The dielectric loss spectrum of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 of the present invention at 1 kHz; Among them: a-change in dielectric loss tanδ of four ceramics in the range of -100℃ to 300℃ at 1kHz; b-comparison of temperature ranges of tanδ≤0.02 of four ceramics at 1kHz; Figure 5 This is the dielectric temperature spectrum of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0026] The present invention provides a barium titanate-based high-entropy dielectric ceramic, which has both low loss and excellent dielectric properties. The chemical composition formula of the barium titanate-based high-entropy dielectric ceramic is (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 - x Sr 0.7 M´ 0.2 TiO 3 , x =0~0.12, M' uses trivalent elements, the trivalent element is Bi 3+ ,La 3 + 、Sm 3+ Any of the elements.

[0027] The barium titanate-based high-entropy dielectric ceramic of the present invention is characterized in that under optimal process conditions, the excellent performance of dielectric loss being always ≤0.02 in the range of -50°C to 300°C can be achieved.

[0028] The present invention also discloses a method for preparing the above-mentioned barium titanate-based high-entropy dielectric ceramic, which is specifically implemented according to the following steps: Step 1: According to the general chemical formula (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 - x Sr 0.7 M´ 0.2 TiO 3 , x = 0~0.12, weigh the raw materials Ba respectively 2 CO 3 、Bi 2 O 3 ,La2 O 3 、 2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O 3 、MgO、Sm 2 O 3 and TiO 2 ; Step 2: placing the raw materials weighed in step 1 in a planetary ball mill, adding anhydrous ethanol as a medium for grinding and drying, and pre-calcining to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor obtained in step 2 is subjected to secondary ball milling, tableting and cold isostatic pressing in sequence, and finally a sheet-shaped ceramic having substantially the same diameter and thickness is obtained; Step 4: The flaky ceramic green body obtained in step 3 is subjected to secondary sintering to obtain a ceramicized barium titanate-based high-entropy dielectric ceramic.

[0029] Preferably, in step 2, the slurry after ball milling is placed in a glass dish for drying for 8 h to 24 h, and during pre-firing, is placed in a muffle furnace for sintering at 800-850° C. for 1 h to 3 h to obtain a ceramic powder precursor.

[0030] Preferably, the two ball millings in step 3 are performed by planetary ball milling, with a rotation speed of 100-500 r / min and a ball milling time of 10 h-24 h; Preferably, in step 3, the pressure of the electric tablet press is 1-5 Pa, and the holding time is 1-3 min; Preferably, the pressure during the cold isostatic pressing process in step 3 is 100-300 MPa, and the holding time is 1-5 min.

[0031] Preferably, during the secondary sintering in step 4, the steel sheet is placed in a muffle furnace and sintered at 1100° C.-1200° C. for 1 h-4 h.

[0032] Preferably, in step 1, Ba is selected 2 CO 3 、Bi 2 O 3 ,La 2 O 3 、 2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O3 、MgO、Sm 2 O 3 and TiO 2 The purity is not less than 99%.

[0033] The barium titanate-based high-entropy dielectric ceramic of the present invention has both low loss and excellent dielectric properties, good temperature stability, high energy storage efficiency and good dielectric properties. x The value of compensates for the volatilization of elements during the sintering process and regulates the doping content of elements at the same time, which is beneficial to obtain excellent energy storage performance and dielectric properties at the same time. Barium titanate-based high-entropy dielectric ceramics have excellent dielectric properties, which is beneficial to obtain ceramics with lower loss and smaller dielectric fluctuations. Anhydrous ethanol is used as the medium and the raw materials are ground by a planetary ball mill and secondary ball milling. The purpose is to make the raw materials mix evenly, and high-speed ball milling is used to further reduce the particle size of the raw materials, which is beneficial to the subsequent sintering reaction. The sample is processed by pre-sintering and secondary sintering. The principle is to use high temperature to increase the driving force to make the chemical elements diffuse and react with each other, so that the ceramics form phases and porcelain, and finally prepare the target component ceramics.

[0034] The chemical composition formula of the barium titanate-based high entropy dielectric ceramic with low loss and excellent dielectric properties is (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 - x Sr 0.7 M´ 0.2 TiO 3 , x =0~0.12, M' uses trivalent elements, the trivalent element is Bi 3+ ,La 3+ 、Sm 3+ Any one of the elements; a method for preparing barium titanate-based high-entropy dielectric ceramics, comprising the steps of ball milling, pre-sintering, tablet pressing and final sintering, wherein the two ball milling times are both 10-24 hours, the electric tablet pressing pressure is 2-5 Pa, the cold isostatic pressing pressure is 100-300 MPa, the pre-sintering process parameters are sintering at 800-850°C for 1-3 hours, and the final sintering process parameters are sintering at 1100-1200°C for 1-4 hours.

[0035] The barium titanate-based high entropy dielectric ceramic prepared by the present invention is characterized by good temperature stability, excellent dielectric properties, high energy storage density, energy storage efficiency exceeding 90%, breakdown electric field greater than 400 kV / cm, the dielectric constant of the ceramic can reach up to about 340, the temperature range of dielectric loss less than 0.02 increases from -25.09~270.20℃ to -57.81~300℃, the temperature stability is improved, and the bandgap width increases from 3.38 eV to 3.48 eV. Therefore, it can be widely used in the field of dielectric energy storage capacitors.

[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0038] Example 1 A method for preparing a barium titanate-based high-entropy dielectric ceramic comprises the following steps: Step 1: Follow (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.04Sr 0.7 Bi 0.2 TiO 3 Ba with a purity higher than 99.5% from Alfa Aesar is weighed in the chemical formula ratio. 2 CO 3 、Bi 2 O 3 、Zr 2 O 3 , Nb 2 O 5 、 2 O 5 、SrCO 3 Sc 2O 3 , MgO, and TiO 2 As raw materials; Step 2: Place the weighed raw materials in a ball mill filled with 1 / 3 zirconium oxide balls, add anhydrous ethanol as a ball milling medium, the ball milling speed is 300r / min, and the ball milling time is 12h; pour the slurry after the ball milling into a culture dish, place it in an oven at 80°C for 12h; put the dried powder into an alumina crucible, cover it and place it in a muffle furnace for pre-sintering to obtain a pre-synthesized powder, set the heating rate to 2°C / min, the pre-sintering temperature to 810°C, and the insulation time to 2h to obtain a ceramic powder precursor; Step 3: The obtained ceramic powder precursor is ball-milled with anhydrous ethanol as the medium at a ball-milling speed of 400 r / min for 36 h. The slurry after ball milling is poured into an evaporating dish and placed in an oven at 80° C. for drying for 12 h. The dried powder is placed in a mortar and fully ground, and then passed through a 100-mesh sieve. The sieved powder is bagged for later use. Weigh 0.24 g of the above powder, put it into a cylindrical mold with a diameter of 10 mm, pre-press it on an electric tablet press at 1 Pa and hold the pressure for 1 min; put the pre-pressed green body into nitrile gloves, evacuate, and then put it into a cold isostatic press at 200 MPa for 1 min to obtain a sheet of ceramic; Step 4: The above-mentioned sheet ceramic is placed in a muffle furnace for high-temperature sintering. The heating rate of the muffle furnace during sintering is 3°C / min, and the sintering temperature is 1160°C for 2 hours, followed by natural cooling with the furnace. During the sintering process, powders of the same component are covered on the ceramic green body to reduce the volatilization of its elements to obtain barium titanate-based high-entropy dielectric ceramics; samples of the sintered barium titanate-based high-entropy dielectric ceramics are respectively ground and polished on 800 mesh, 1500 mesh and 2000 mesh sandpaper; silver paste is applied to the upper and lower surfaces of the sample, and then placed in a muffle furnace at 500°C for 30 minutes for testing its electrical properties.

[0039] Example 2 A method for preparing a barium titanate-based high-entropy dielectric ceramic comprises the following steps: Step 1: Follow (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.04Sr 0.7 La 0.2 TiO 3 Ba with a purity higher than 99% from Alfa Aesar is weighed in the chemical formula ratio.2 CO 3 、Bi 2 O 3 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 ,La 2 O 3 、 2 O 5 Sc 2 O 3 , MgO, and TiO 2 As raw materials; Step 2: Place the weighed raw materials in a ball mill filled with 1 / 3 zirconia balls, add anhydrous ethanol as a ball milling medium, the ball milling speed is 400r / min, and the ball milling time is 12h; pour the slurry after the ball milling into a culture dish, place it in an oven at 80°C for 12h; put the dried powder into an alumina crucible, cover it and place it in a muffle furnace for pre-sintering to obtain a pre-synthesized powder, set the heating rate to 2°C / min, the pre-sintering temperature to 810°C, and the insulation time to 4h to obtain a ceramic powder precursor; Step 3: The obtained ceramic powder precursor is ball-milled with anhydrous ethanol as the medium at a ball-milling speed of 400 r / min for 36 h. The slurry after ball milling is poured into an evaporating dish and placed in an oven at 80° C. for drying for 12 h. The dried powder is placed in a mortar and fully ground, and then passed through a 100-mesh sieve. The sieved powder is bagged for later use. Weigh 0.25 g of the above powder, put it into a cylindrical mold with a diameter of 10 mm, pre-press it on an electric tablet press at 2 Pa and hold the pressure for 2 minutes; put the pre-pressed green body into nitrile gloves, evacuate it, and then put it into a cold isostatic press at 200 MPa for 1 minute to obtain a sheet of ceramics; Step 4: placing the above-mentioned sheet-like ceramic in a muffle furnace for high-temperature sintering, the sintering temperature of the muffle furnace is 1200°C for 4 hours, and then naturally cooling with the furnace. During the sintering process, the powder of the same component is covered on the ceramic green body to reduce the volatilization of its elements, so as to obtain barium titanate-based high-entropy dielectric ceramics; the obtained barium titanate-based high-entropy dielectric ceramic samples are respectively ground and polished on 800 mesh, 1200 mesh and 2000 mesh sandpaper; silver is coated on the upper and lower surfaces of the sample, and then placed in a muffle furnace at 550°C for 20 minutes for testing dielectric properties; Pt electrodes are sputtered on the surface of the sample using a magnetron sputtering instrument for testing hysteresis loops; The X-ray diffraction pattern of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 is as follows: Figure 1As shown in the figure, it can be seen that the BNT-based ceramics prepared by the present invention have a perovskite structure and no second phase exists. It can be seen that the formula ratio of the present invention is effective, the preparation process is reasonable, and the doping elements have successfully entered the corresponding lattice.

[0040] The scanning electron microscope photo of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 is as follows: Figure 2 As shown in the figure, it can be seen that the ceramic presents a dense microstructure, the grain size is about 2 microns, and there are few pores on the ceramic surface, which proves that the ceramic is densely bonded after sintering, so the ceramic has a high breakdown electric field.

[0041] The temperature-dependent Raman spectrum of the barium titanate-based high-entropy dielectric ceramics prepared in Example 2 is as follows: Figure 3 As shown in the figure, it can be seen that the Raman spectrum does not produce new Raman peaks with the change of temperature, indicating that the structure of the ceramic sample is stable and does not change with temperature. As the temperature changes, the positions of all peaks do not change, indicating that the ceramic sample has good temperature stability.

[0042] The dielectric temperature spectrum of the barium titanate-based high entropy dielectric ceramic prepared in Example 2 is as follows: Figure 4 As shown in the figure, it can be seen that by comparing the dielectric loss (tanδ) of the ceramic samples, it is found that with the increase of SLT content, the dielectric loss gradually decreases, and the temperature range where the dielectric loss is less than 0.02 gradually increases. 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 )Ceramic, BTH-0.04SLT((Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.04Sr 0.7 La 0.2 TiO 3 )Ceramic, BTH-0.08SLT((Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta0.01 ) 3 -0.08Sr 0.7 La 0.2 TiO 3 )Ceramic and BTH-0.12SLT((Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.12Sr 0.7 La 0.2 TiO 3 ) The temperature range of the dielectric loss tanδ less than 0.02 for ceramic samples is -25.09~270.20℃, -33.00~300℃, -46.18~300℃ and -57.81~300℃. It is found that with the increase of SLT content, the temperature range of dielectric loss tanδ≤0.02 gradually increases. Among them, the temperature range of dielectric loss less than 0.02 for BTH-0.12SLT ceramic sample is the largest, and the dielectric loss has excellent temperature stability.

[0043] Example 3 A method for preparing a barium titanate-based high-entropy dielectric ceramic comprises the following steps: Step 1: Follow (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.12Sr 0.7 La 0.2 TiO 3 Ba with a purity higher than 99% from Alfa Aesar is weighed in the chemical formula ratio. 2 CO 3 、Bi 2 O 3 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 ,La 2 O 3 、 2 O 5 Sc 2 O 3 , MgO, and TiO 2 As raw materials; Step 2: Place the weighed raw materials in a ball mill filled with 1 / 3 zirconia balls, add anhydrous ethanol as a ball milling medium, the ball milling speed is 300r / min, and the ball milling time is 36h; pour the slurry after the ball milling into a culture dish, place it in an oven at 80°C for drying for 24h; put the dried powder into an alumina crucible, cover it and place it in a muffle furnace for pre-sintering to obtain a pre-synthesized powder, set the heating rate to 3°C / min, the pre-sintering temperature to 820°C, and the insulation time to 4h to obtain a ceramic powder precursor; Step 3: The obtained ceramic powder precursor is ball-milled with anhydrous ethanol as the medium at a ball-milling speed of 300 r / min for 36 h. The slurry after ball milling is poured into an evaporating dish and dried in an oven at 80° C. for 24 h. The dried powder is fully ground in a mortar and then passed through a 100-mesh sieve. The sieved powder is bagged for later use. Weigh 0.24 g of the above powder, put it into a cylindrical mold with a diameter of 10 mm, pre-press it on an electric tablet press at 5 Pa and hold the pressure for 2 minutes; put the pre-pressed green body into nitrile gloves, evacuate, and then put it into a cold isostatic press at 150 MPa for 2 minutes to obtain a sheet of ceramics; Step 4: Place the above-mentioned sheet ceramic in a muffle furnace for high-temperature sintering. During the sintering, the sintering temperature of the muffle furnace is 1200°C and kept warm for 2 hours, and then naturally cool with the furnace. During the sintering process, powders of the same component are covered on the ceramic green body to reduce its element volatilization to obtain barium titanate-based high-entropy dielectric ceramics; samples of the sintered barium titanate-based high-entropy dielectric ceramics are thinly polished on 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively; silver paste is applied to the upper and lower surfaces of the sample, and then placed in a muffle furnace and kept warm at 500°C for 30 minutes to test its electrical properties.

[0044] Example 4 A method for preparing a barium titanate-based high-entropy dielectric ceramic comprises the following steps: Step 1: Follow (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 ) 3 -0.08Sr 0.7 Sm 0.2 TiO 3 Ba with a purity higher than 99% from Alfa Aesar is weighed in the chemical formula ratio. 2 CO 3 、Bi 2 O 3 、2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O 3 、MgO、Sm 2 O 3 and TiO 2 As raw materials; Step 2: Place the weighed raw materials in a ball mill filled with 1 / 3 zirconia balls, add anhydrous ethanol as a ball milling medium, the ball milling speed is 400r / min, and the ball milling time is 12h; pour the slurry after the ball milling into a culture dish, place it in an oven at 80°C for 12h; put the dried powder into an alumina crucible, cover it and place it in a muffle furnace for pre-sintering to obtain a pre-synthesized powder, set the heating rate to 5°C / min, the pre-sintering temperature to 840°C, and the insulation time to 4h to obtain a ceramic powder precursor; Step 3: The obtained ceramic powder precursor is ball-milled with anhydrous ethanol as the medium at a ball-milling speed of 150 r / min for 36 h. The slurry after ball milling is poured into an evaporating dish and dried in an oven at 80° C. for 12 h. The dried powder is fully ground in a mortar and then passed through a 100-mesh sieve. The sieved powder is bagged for later use. Weigh 0.24 g of the above powder, put it into a cylindrical mold with a diameter of 10 mm, pre-press it on an electric tablet press at 3 Pa and hold the pressure for 1 min; put the pre-pressed green body into nitrile gloves, evacuate it, and then put it into a cold isostatic press at 200 MPa for 1 min to obtain a sheet of ceramics; Step 4: The above-mentioned sheet ceramic is placed in a muffle furnace for high-temperature sintering. During the sintering, the sintering temperature of the muffle furnace is 1100°C and kept warm for 3 hours, and then naturally cooled with the furnace. During the sintering process, powders of the same component are covered on the ceramic green body to reduce its element volatilization to obtain barium titanate-based high-entropy dielectric ceramics; samples of the sintered barium titanate-based high-entropy dielectric ceramics are respectively ground and polished on 800 mesh, 1500 mesh and 2000 mesh sandpaper; silver paste is applied on the upper and lower surfaces of the sample, and then placed in a muffle furnace at 520°C for 30 minutes for testing its electrical properties.

[0045] Example 5 A method for preparing a barium titanate-based high-entropy dielectric ceramic comprises the following steps: Step 1: Follow (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04Nb 0.05 Ta 0.01 ) 3 -0.12Sr 0.7 Sm 0.2 TiO 3 Ba with a purity higher than 99% from Alfa Aesar is weighed in the chemical formula ratio. 2 CO 3 、Bi 2 O 3 、 2 O 5 、Zr 2 O 3 , Nb 2 O 5 、SrCO 3 Sc 2 O 3 、MgO、Sm 2 O 3 and TiO 2 As raw materials; Step 2: Place the weighed raw materials in a ball mill filled with 1 / 3 zirconia balls, add anhydrous ethanol as a ball milling medium, the ball milling speed is 200r / min, and the ball milling time is 24h; pour the slurry after the ball milling into a culture dish, place it in an oven at 100°C for drying for 24h; put the dried powder into an alumina crucible, cover it and place it in a muffle furnace for pre-sintering to obtain a pre-synthesized powder, set the heating rate to 3°C / min, the pre-sintering temperature to 860°C, and the insulation time to 2h to obtain a ceramic powder precursor; Step 3: The obtained ceramic powder precursor is ball-milled with anhydrous ethanol as the medium at a ball-milling speed of 200 r / min for 24 h. The slurry after ball milling is poured into an evaporating dish and dried in an oven at 100° C. for 24 h. The dried powder is fully ground in a mortar and then passed through a 100-mesh sieve. The sieved powder is bagged for later use. Weigh 0.24 g of the above powder, put it into a cylindrical mold with a diameter of 10 mm, pre-press it on an electric tablet press at 4 Pa ​​and keep the pressure for 2 minutes; put the pre-pressed green body into nitrile gloves, evacuate it, and then put it into a cold isostatic press at 300 MPa for 2 minutes to obtain a sheet of ceramics; Step 4: Place the above-mentioned sheet ceramic in a muffle furnace for high-temperature sintering. During the sintering, the sintering temperature of the muffle furnace is 1250°C and kept warm for 2 hours, and then naturally cool with the furnace. During the sintering process, powders of the same component are covered on the ceramic green body to reduce its element volatilization to obtain barium titanate-based high-entropy dielectric ceramics; the samples of the sintered barium titanate-based high-entropy dielectric ceramics are respectively ground and polished on 800 mesh, 1500 mesh and 2000 mesh sandpaper; silver paste is applied on the upper and lower surfaces of the sample, and then placed in a muffle furnace at 600°C for 15 minutes to test its electrical properties.

[0046] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A barium titanate-based high entropy dielectric ceramic, characterized in that: The chemical composition formula of the barium titanate-based high entropy dielectric ceramic is (Ba 0.8 Bi 0.2 )(Ti 0.58 Zr 0.14 Sc 0.18 Mg 0.04 Nb 0.05 Ta 0.01 )O3- x Sr 0.7 M´ 0.2 TiO3; in, x =0~0.12; M´ is a trivalent element, and the trivalent element is Bi 3+ ,La 3+ and Sm 3+ Any of .

2. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 1, characterized in that: The following steps are involved: According to the stoichiometric ratio of the general chemical composition formula of barium titanate-based high entropy dielectric ceramics, raw materials Ba2CO3, Bi2O3, La2O3, Ta2O5, Zr2O3, Nb2O5, SrCO3, Sc2O3, MgO, Sm2O3 and TiO2 are weighed; Pre-treating the weighed raw materials to obtain a ceramic powder precursor; After post-processing the ceramic powder precursor, a flaky ceramic is obtained; The flaky ceramics are sintered to obtain barium titanate-based high-entropy dielectric ceramics.

3. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 2, characterized in that: The pretreatment includes a ball milling process, a grinding and drying process with anhydrous ethanol as a medium, and a pre-calcination process, which are performed in sequence.

4. The method for preparing a barium titanate-based high-entropy dielectric ceramic according to claim 3, characterized in that: The grinding and drying process takes 8-24 hours. The pre-sintering treatment is sintering at 800-850° C. for 1-3 hours.

5. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 3, characterized in that: The post-treatment includes ball milling, tableting and cold isostatic pressing performed in sequence.

6. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 5, characterized in that: The tableting pressure is 1-5 Pa, and the holding time is 1-3 min; The pressure during the cold isostatic pressing process is 100-300 MPa, and the holding time is 1-5 min.

7. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 5, characterized in that: The ball milling process is performed at a rotation speed of 100-500 r / min and a time of 10-24 h.

8. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 2, characterized in that: The sintering process is sintering at 1100-1200° C. for 1-4 hours.

9. The method for preparing a barium titanate-based high entropy dielectric ceramic according to claim 2, characterized in that: The purity of the raw materials Ba2CO3, Bi2O3, La2O3, Ta2O5, Zr2O3, Nb2O5, SrCO3, Sc2O3, MgO, Sm2O3 and TiO2 is not less than 99%.

10. The use of a barium titanate-based high entropy dielectric ceramic in a dielectric energy storage capacitor according to claim 1, characterized in that: When the application temperature is between -50°C and 300°C, the dielectric loss of the barium titanate-based high entropy dielectric ceramic is always ≤0.02 when used in a dielectric energy storage capacitor.

Citation Information

Patent Citations

  • Barium titanate-based multilayer dielectric material with high energy storage density and preparation method thereof

    CN118063207A

  • Method for preparing sodium bismuth titanate-based high-temperature capacitor medium ceramic

    CN108585837A

  • High-electric-field-resistant high-energy-density barium titanate-based relaxor ferroelectric ceramic material and preparation method thereof

    CN110642617A

  • Ceramic material as well as preparation method and application thereof

    CN112876240A

  • Barium titanate-based high-entropy lead-free relaxor ferroelectric energy storage ceramic and preparation method thereof

    CN118344145A